(untitled) (Fiep Bulletin - online, 2015)
The article under the pedagogic aspect of motricity human in the social historic dimension focus on the university teaching. The objective is to accomplish the analysis of teaching to verify the satisfaction level of the students in the discipline of Recreation at UNIABEU with the Cooperative Games. Those games has the intention to practice over the Physical Education quality of life, besides that cultivate peace through the parallelism to the pedagogic of competitive deport. In the methodology it was applied one questionnaire already valid by Nunes (2004), besides film version. To the analysis of the content it was used Bardin (1977), where it was classified 8 (eight) categories represented by graphics and tables. Concluding, the study demonstrate total satisfaction of the students, because it gives an effective opportunity in physical activity, pleasure and necessity to do it, valorizing its importance in the development of the Physical Education professional.